Physical and Chemical Characterization of Manalagi Apple (Malus sylvestris Mill) Leather Enriched with Either Mango, Pineapple or Dragon Fruit - Mokhamad Nur; Siti Sulaihah; Mohd Zuhair Mohd Nor (Universitas Negeri Malang, 2022)
Manalagi apple leather can be an innovation for new processed products made from fruit pulp and undergo a drying process. The main problem is that apple leather has a less plastic texture, non-variative color and taste, and stickiness. For this reason, in this study other fruits were added in certain proportions and food additives such as arabic gum and maltodextrin to improve the physicochemical and organoleptic characteristics of manalagi apple leathers. This study used the Split-split Plot Design method with three factors. Factor I is a type of fruit (red dragon fruit, pineapple, mango), factor II is the variation in proportion ((25:75) percent, (50:50) percent, (75:25) percent), factor III is maltodextrin concentration (5, 10, and 15 percent). The best treatment was taken from each type of fruit substitution, so there were 3 the best treatment: apple leather 1) enriched with 50 percent dragon fruit and 10 percent maltodextrin, 2) enriched with 75 percent pineapple and 10 percent maltodextrin, and 3) enriched with 75 percent mango and 10 percent maltodextrin.DOI: 10.17977/um024v7i22022p116